أسس التكوين في رسوم طلبة قسم التربية الأسرية والمهن الفنية - جابر روناك عبود; كاظم نجلاء محمد (lark, 2019)
Abstract The present research aimed at identifying the foundations of configuration in family education students fees and professional College of basic education in Rajasthan University. To achieve the goal of research the researcher has chosen a sample of fourth grade students fees/matinee and posed (30) draw students spread over two halls and are the original community as a whole, the researcher established fees analysis form building b (9) paragraphs, achieving virtual assented and consistency depending on route Agreement with the observers on the tool. Layer analysis of fees in accordance with the format in the date 7/1/2019, then apply the percentage formula and results in high use realistic design and diffuse authority and sovereignty to adopt unity and harmony with all its branches at the Department students fees